The Corruption Investigation In The Regional Police of Riau Islands, Indonesia - Hardianto Djanggih; Hambali Thalib; Ahmad Ramadhan (Universitas Muhammadiyah Sidoarjo, 2017)
This research aim to analyzes the authority of the Regional Police of Riau Islands in a criminal act of corruption investigation. The method used is normative-empirical research. The results found that investigation of criminal corruption in Regional Police of Riau Islands conducted according to the authority of police investigators. In addition to proving the deeds of perpetrator, criminal investigation of corruption is also a means of restoring the state's financial losses as much as possible. In its implementation, corruption criminal investigation is influenced by legal factors, law enforcement factors, supporting facilities or facilities supporting law enforcement, community factors, and cultural factor.